Handbook of reading interventions - O'Connor, Rollanda E.; Vadasy, Patricia (The Guilford Press, 2011)
"Comprehensive, authoritative, and designed for practical utility, this handbook presents evidence-based approaches for helping struggling readers and those at risk for literacy difficulties or delays. Leading experts explain how current research on all aspects of literacy translates into innovative classroom practices. Chapters include clear descriptions of effective interventions for word recognition, spelling, fluency, vocabulary, comprehension, and writing, complete with concrete examples and teaching scripts. Coverage also encompasses preschool literacy instruction and interventions for older readers, English language learners, and students with learning disabilities, as well as peer-mediated and tutoring approaches"-- Provided by publisher.